2021
DOI: 10.1093/ptj/pzab231
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Total Joint Arthroplasty on Long-Term Physical Activity: A Secondary Analysis of the Health and Retirement Study

Abstract: Objective Physical inactivity is the fourth leading cause of global mortality and is prevalent among people with lower extremity osteoarthritis. Lower extremity osteoarthritis is the most common arthritis type afflicting older adults, and total joint arthroplasty (TJA) performed to address the condition is Medicare’s largest annual expense. Despite TJA intervention to address the disabling effects of osteoarthritis, physical activity (PA) level remains stable 6 months after TJA; however, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In our study, 63% of therapists were fully adherent with the clinical practice guideline, and partial adherence could mostly be attributed to not using aerobic exercise training. This is a potential opportunity for improvement for those patients to become more physically active, with corresponding substantial health benefits, because decreased activity levels preoperatively will not automatically increase after the procedure (LeDoux et al, 2022;Paxton et al, 2015). In fact, the study of Groen et al (2012) showed that 42% of patients with a TKA (n = 830) were not active enough 1 year postoperatively and beyond to meet the recommended physical activity level that promotes health (Groen et al, 2012;Health (Wainwright et al, 2020) also ensures that PT in the outpatient practice starts at an earlier postoperative stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, 63% of therapists were fully adherent with the clinical practice guideline, and partial adherence could mostly be attributed to not using aerobic exercise training. This is a potential opportunity for improvement for those patients to become more physically active, with corresponding substantial health benefits, because decreased activity levels preoperatively will not automatically increase after the procedure (LeDoux et al, 2022;Paxton et al, 2015). In fact, the study of Groen et al (2012) showed that 42% of patients with a TKA (n = 830) were not active enough 1 year postoperatively and beyond to meet the recommended physical activity level that promotes health (Groen et al, 2012;Health (Wainwright et al, 2020) also ensures that PT in the outpatient practice starts at an earlier postoperative stage.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 63% of therapists were fully adherent with the clinical practice guideline, and partial adherence could mostly be attributed to not using aerobic exercise training. This is a potential opportunity for improvement for those patients to become more physically active, with corresponding substantial health benefits, because decreased activity levels preoperatively will not automatically increase after the procedure (LeDoux et al., 2022; Paxton et al., 2015). In fact, the study of Groen et al.…”
Section: Discussionmentioning
confidence: 99%
“…While evidence has suggested that physical activity (PA) in patients with OA may improve both joint pain and function, as well as other comorbid conditions and quality of life [4], the associated discomfort may limit these patients from achieving recommended levels of PA. Authors have reported that the majority of patients with OA do not meet guideline recommendations for daily activity [5,6], performing less PA than age-matched subjects without OA [7]. In addition, several reports have suggested that these patients spend the majority of their time in sedentary behaviors [8][9][10], which has been shown to significantly impact the risk of morbidity and mortality in adult populations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise is prescribed for symptomatic improvement once surgery is recommended for end-stage OA; however, this has shown equivocal results on function when implemented either before surgery or following surgery [6]. While people describe improvements in a range of patient's reported outcomes after hip and knee arthroplasty, improvements in physical activity levels are not seen [7], and physical activity interventions delivered after surgery are not effective [8].…”
Section: Introductionmentioning
confidence: 99%